Effect heat treatment and addition Lactobacillus acidophilus on the processing brie cheese (Research, Society and Development, 2021)
Brie cheese is a product with good acceptance in Brazil, the estimate is that this class of cheese represents about 3% of the world cheese production. This work aimed to develop brie cheeses with raw and pasteurized milk added with probiotic culture, consisting of Lactobacillus acidophilus, initial culture Lactococcus lactis, secondary culture Penicillium candidum, as well as to evaluate the effect of heat treatment and the addition of probiotic culture in physical-chemical characteristics and electrophoretic profile after thirty days of maturation, at 10 ºC. Brie cheeses were processed in batches, with five formulations being processed. Physical-chemical characterizations and electrophoretic profile were carried out, as well as the viability of the probiotic culture of L. acidophilus after maturation. The samples with heat treatment showed different characteristics from those obtained with raw milk, reflecting in the physical-chemical composition of the cheeses. The relative electrophoretic mobility, position of the protein bands, and their respective molecular weights in greater abundance in the cheeses were identified as: α S1-casein (23.61 kDa), α S2-casein (25.23 kDa), β-casein (23.98 kDa), к-casein (19.02 kDa) and α-lactalbumin (14.2 kDa). In all cheeses obtained, the microorganism Lactobacillus acidophilus showed viability of the microorganism above the recommended minimum, in the order of 107 CFU / g. Which shows that brie cheese is a good matrix for the probiotic analyzed.